Am80, a retinoic acid receptor agonist, ameliorates murine vasculitis through the suppression of neutrophil migration and activation. Issue 2 (28th January 2013) - Miyabe, Chie; Miyabe, Yoshishige; Miura, Noriko N.; Takahashi, Kei; Terashima, Yuya; Toda, Etsuko; Honda, Fumiko; Morio, Tomohiro; Yamagata, Naoko; Ohno, Naohito; Shudo, Koichi; Suzuki, Jun‐Ichi; et al.
Abstract: Objective: Vasculitis is characterized by leukocyte infiltration in the vessel walls, with destructive damage to mural structures. Retinoids are compounds that bind to retinoic acid receptors and exert biologic activities similar to those of vitamin A, including modulatory effects on cell proliferation and differentiation. This study was undertaken to examine the therapeutic effects of a synthetic retinoid, Am80, in a murine model of vasculitis induced by Candida albicans water‐soluble fraction (CAWS). Methods: Vasculitis was induced in BALB/c mice by intraperitoneal injection of CAWS. Neutrophils were depleted by injection of antineutrophil antibody–positive serum. Am80 was administered orally once daily. Vasculitis was evaluated histologically. Migration of labeled adoptively transferred cells was quantified. Chemotaxis was assessed by cell mobility analysis. Production of reactive oxygen species (ROS) and phosphorylation of MAPKs were measured by flow cytometry. Concentrations of elastase were measured by enzyme‐linked immunosorbent assay. Results: Administration of CAWS induced vasculitis in the coronary arteries and aortic root, with abundant neutrophil infiltration. Depletion of neutrophils reduced CAWS‐induced vasculitis. Treatment with Am80 led to a significant attenuation of the vasculitis score and inhibition of the migration of transferred neutrophils into the site of vasculitis. In vitro, Am80 suppressed fMLP‐induced chemotaxis of human peripheral blood neutrophils. ROS production and elastase release by stimulated neutrophils were reduced by AM80 treatment, and Am80 also inhibited phosphorylation of ERK‐1/2 and p38 in neutrophils stimulated with fMLP plus lipopolysaccharide. Conclusion: Am80 significantly suppressed CAWS‐induced vasculitis. This effect was presumably exerted via inhibition of neutrophil migration and activation.